Manajemen Krisis Komunikasi dalam Isu Transparansi Kompetisi Sains Madrasah (KSM) 2024 - Yuyun Wulandari (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
The 2024 Madrasah Science Competition (KSM) faced transparency issues that affected public trust in its organisation. This study aims to identify the communication crisis management approach applied, evaluate the effectiveness of the strategies used, and analyse the short and long term impact of this crisis on the image of KSM. Using Situational Crisis Communication Theory (SCCT), this study found that accountability-based communication strategies, technology utilisation, and stakeholder collaboration were effective in mitigating the crisis. The results of the study are expected to serve as a guide for similar competition organisers in facing transparency challenges.